NATURAL GERMINATION AS RESILIENCE COMPONENT IN MEDITERRANEAN COPPICE STANDS OF CASTANEA-SATIVA MILL AND QUERCUS-ILEX L (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 1994)
In the Mediterranean basin, most of the present forests derive from original forests where the dominant species was different from the present one. These changes are largely due to human activities reflecting millenia of management and, often, overexploitation. In southern France, for example, palaeoecologists believe that the original malacophyllous deciduous forest of downy oak (Quercus pubescens) was replaced by a sclerophyllous evergreen holm oak (Quercus ilex) coppice in the driest areas, and chestnut (Castanea sativa) orchards or coppices in the `'wettest'' areas. However, for the last several decades, exploitation of these coppice stands has been decreasing. In this study, we addressed the question of the resilience of these managed ecosystems in the fact of changing management schemes, and to determine appropriate strategies and criteria of sustainable development. We present some aspects of the auto-succession after clearcutting of holm oak coppice stands and aspects of the natural regeneration of 4 species (Q. ilex, Q. pubescens, C. sativa, and P. pinaster). The consequences of the contrasted life history strategies are compared to estimate the future of these coppices.

Germination and regeneration mechanisms in Mediterranean degenerate forests (Journal of Vegetation Science, 1993)
Abstract. Germination and developmental behaviour during juvenile stages are of importance in relation to succession mechanisms acting on plant communities. This is particularly so in the Mediterranean region, where the climatic summer drought causes stress. We investigated and compared germination and development of four tree species in two parts of the French Mediterranean region where the original dominant tree species (Quercus pubescens) has been largely replaced by Quercus ilex in the southern part, and Castanea sativa in the northern part. Observed differences in germination rates and developmental behaviour, especially shootroot ratio and the role of water supply, suggest that other species may eventually replace the current dominant species.

NATURAL DEGENERATE MEDITERRANEAN FORESTS - WHICH FUTURE - THE EXAMPLES OF THE HOLM OAK (QUERCUS-ILEX L) AND CHESTNUT (CASTANEA-SATIVA MILL) COPPICE STANDS (RESPONSES OF FOREST ECOSYSTEMS TO ENVIRONMENTAL CHANGES, 1992)
Primarily derived from the Quercus pubescens forest destroyed by overexploitation, the Quercus ilex and Castanea sativa coppice stands are two of the most widespread biocoenoses in the European Mediterranean area. Two of the questions we sought to answer were (i) in the case where the same disturbance persists, whether these coppice stands reach a state of “equilibrium” based on auto-succession or they continue to change, and (ii) in the case where disturbance stops, whether the present dominant species (Q. ilex or C. sativa) continues to be dominant (high resilience) or an other species (Q. pubescens ?) could replace it. A third case exists, i.e. a change of the “disturbance” in order to obtain a “sustainable” development, but, in that case, biological or socio-economical criteria must be defined. In order to highlight the first stages of these possible changes, germination abilities of these species were studied and compared. For Q. ilex coppice stands, it can be said that there would appear to be a partial allelopathic inhibition of Q. ilex germination, to which Q. pubescens is less sensitive. For C. sativa, this phenomenon was not found. We also briefly discuss the main characteristics of a programme which tests some biological criteria for a sustainable development.